POLITENESS IN ACCEPTING AND REJECTING OPINIONS: INSIGHTS FROM 4th QATAR INTERNATIONAL ARABIC DEBATE VIDEOS FOR ARABIC SPEAKING LESSONS - Nudya Kuntum Khoirel Abidah (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2024)
Abstract: Qatar International Arabic Debate is a prestigious event and a reference in the practice of Arabic debate in the world. Participants who enter the event are the best representatives of countries in the world. Therefore, the ability to speak Arabic is good, besides that in delivering, accepting, and rejecting arguments in the debate has been arranged in a good systematic and polite manner. The researcher is interested in examining the sentence patterns used in accepting and rejecting opinions in Arabic debates with the aim that the results of the analysis can be utilised in speaking practice in Arabic language classes. To diversify the ways of teaching speaking skills and improve students' efficiency in expressing opinions with the beauty of correct Arabic. This research uses a qualitative method with listening and note-taking techniques and uses classification referring to Leech's concept of appropriateness. The results of this study show that the words uttered in the Arabic scientific debate have a good and polite systematic in accepting and rejecting the opponent's opinion. In addition, this research produces a formulation of Arabic sentence patterns and teaching methods that are ready to be used in the practice of learning to speak Arabic through classroom debates. So that the results of this research are applicable and useful for a wider audience. Keywords: Discourse analysis, Politeness in speech, International Arabic Qatar Debate, Arabic Speaking